Analisis Model Pembelajaran Multiliterasi dalam Meningkatkan Kualitas Pemahaman Membaca Siswa - Hotmasarih Harahap; Mardianto Mardianto; Muhammad Irwan Padli Nasution (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The low level of understanding and writing ability of students causes students to find it difficult to accept, absorb, and understand existing lessons. This will also have an impact on the inability of students to deal with problem solving. Therefore, it is necessary to do an appropriate learning model. However, at this time there are still many educators who do not know an effective learning model to enable students to master reading comprehension skills. The solution in this case is to apply a multiliteracy learning model to hone students' higher-order thinking skills and improve their writing skills. Because this is a competency capital that must be possessed in facing the digital era of the 21st century. The purpose of this research is to find out the multiliteracy learning models that will be applied by educators to students. This research is a type of literature study qualitative research. By using primary sources derived from books and articles related to the multiliteracy learning model. The results of this study are textual, visual, musical, digital literacy models, understanding and skill representation models as well as supporting learning process models that can improve students' reading comprehension and critical thinking.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//